Integracja polityczna Polaków na emigracji. Polonia w Austrii – studium przypadku - Nowak, Ewa; Bernacka, Ryszarda Ewa; Riedel, Rafał (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
The main purpose of the survey discussed in this paper is to answer the question of which factors describe the status of political integration of Poles in Austria. Political integration concerns the phenomenon of joining the political life of a given political system and, to some extent, also its results. For the purpose of this study the notion of political integration is to stand for the involvement of the ‘visiting’ citizens in the political life of the ‘host’ state, in particular political participation, taking the form of public activity and voting in elections. The survey adopts a general theoretical model where the state of integration of Poles in Austria is comprehended in terms of a three-element political culture (comprising cognitive, emotional-and-assessing, and behavioral elements). It undergoes external influences, related to the period spent living abroad, and domestic influences of social identity (approached functionally). Additionally, the model assumes that these factors can be internally related. The empirical aspect of the analysis is based on the authors’ own survey carried out using a questionnaire, psychological scale and focus group interview of a sample of Polish émigrés in Austria.
Political integration of Polish émigrés. Polonia in Austria – a case study